An analysis of recent severe climate events over Tanzania - Kijazi, Agnes Lawrence (Department of Oceanography, 2024)
This thesis focuses on the analysis of the recent severe climate events over Tanzania. The circulation patterns over the Atlantic and Indian oceans responsible for inter-annual and intra-seasonal rainfall variability in Tanzania were analysed and the skill of Global Circulation Model (GCM) in capturing the inter-annual variability assessed. The results were tailored to the application for agriculture over North-eastern Tanzania to aid decision makers in the formulation of agriculture related policies for sustainable development. The thesis first touches on an analysis of the mean characteristics of selected meteorological fields comprising both MAM and OND rainfall seasons. Such processes were examined as necessary background information to determine the causes of rainfall variability. Two regions of deep convection were observed: one maritime (over the Indian Ocean), and one continental (over the Congo forests). High values of latent heat flux occurred in the Congo forests during the OND season, suggesting this region to be among the sources of moisture for said season. Generally, the easterly moisture flux dominates the region for both the OND and MAM seasons and this suggests the Indian Ocean to be the main source of moisture for the country's rainfall. The descending branch of the Walker type circulation was located over the Indian Ocean at about 55 °E and longitudinal shifts of this branch may cause rainfall anomalies. Similarly, the departure from any observed mean characteristics may cause climate anomalies over the region. Inter-annual time scale analysis indicates that the region experienced more dry than wet years during the period of study. However, dry anomalies were much weaker than wet anomalies, and the influence of El Niño on wet anomalies was suggested as one of the causes of this variation. Ascent (descent) over the study region coupled with a strong moisture flux convergence (divergence) was observed to be the dominant feature for wet (dry) years. On the intra-seasonal time scale that is so important for agricultural planning, wet years were characterised by longer than normal rainfall seasons, while for dry years the seasons were shorter than average. For the dry OND season, an out-of-season peak was evident that could be used to minimize the effect of drought. The circulation features show that the wet years were characterised by a cyclonic moisture flux and wind over the tropical South Indian Ocean east of Madagascar coupled with strong westerly moisture flux emanating from the equatorial Atlantic Ocean and south-easterly moisture flux from the Western Indian Ocean that enhance moisture flux convergence over the country. In contrast, the dry years show more or less the reverse circulation patterns over the Indian Ocean. An anticyclonic circulation occurs east of Madagascar with circulation patterns that divert moisture away from Tanzania. Comparison of ECHAM 4.5 model with NCEP/NCAR reanalysis over the study region indicated that the model was able to represent the circulation features associated with rainfall during the wet season while for the dry season the model failed to represent the circulation features. This suggests that local features (that are not well captured by the model) contribute significantly to the rainfall variability over the region, especially during dry seasons. The results obtained from this thesis have contributed to a better understanding of the mechanisms associated with rainfall variability over north eastern Tanzania. The research has addressed the gap that exists in the literature concerning what factors and mechanisms might drive rainfall variability at the sub-regional scale over East Africa. Furthermore, this study is the one of the first to assess the ability of an atmospheric model to replicate the observed circulation and rainfall patterns at this sub-regional scale for Tanzania.